Treatment of a cyanide-free copper electroplating solution by electrodialysis: study of ion transport and evaluation of water and inputs recovery. - Scarazzato, Tatiana (2017)
The two most common commercial copper baths are the acid sulfate copper bath and the alkaline cyanide copper bath. Alkaline copper baths are mostly used to coat parts with complex geometry and to avoid galvanic deposition when depositing a metal on a less noble substrate. Because of the toxicity of cyanide compounds, alternative baths have been developed using different complexing agents. The starting point of the present study is a cyanide-free strike bath developed for copper plating on Zamak substrates developed by the Institute for Technological Research of the State of São Paulo/ Brazil. The replacement of a raw material such as cyanide must be economically advantageous and technically feasible. Therefore, this study intended to propose an alternative to the treatment of liquid wastes from the mentioned bath, aiming at simultaneous water reclamation and chemicals recovery in a closed system. The electrodialysis membrane separation process was studied, using a laboratoryscale system operating with a synthetic solution simulating the rinsing waters from the HEDP-based bath. The feasibility of the technique was evaluated by analyzing operational parameters such as ion extraction, demineralization rate, concentration rate, current efficiency for each anionic specie and average energy consumption. Because HEDP is a chelating agent, the transport of Cu(II)-HEDP chelates through anion-exchange membranes was also evaluated by means of electrochemical methods. Chronopotentiometric and current-voltage curves were constructed for different model solutions containing the same compounds as the original bath. A relation between the presence of chelates in the solutions and the fixed ion exchange group could be established. Lastly, deposition tests were performed using electrolytes containing the recycled inputs and the characteristics of the coatings were analyzed. The results showed that an electrodialysis stack using strongly basic anion-exchange membranes was suitable to produce treated solutions and a concentrate containing the ions from the bath. The concentrate could be added to the copper bath to compensate eventual drag-out losses without affecting the quality of the coatings. Thus, the application of electrodialysis was shown to be a feasible alternative for recovering water and inputs from the evaluated solution, reducing the wastewater generation and saving natural resources.